Graphical pinch analysis for planning biochar-based carbon management networks - Tan, Raymond Girard R. (Animo Repository, 2018)
Biochar is a potentially scalable negative emission technology (NET). The negative net flow of carbon is achieved sequentially via photosynthesis which fixes atmospheric carbon into biomass, followed by thermochemical processing of biomass into biochar which converts the bulk of the fixed carbon into stable or recalcitrant form, and finally by the application of the resulting biochar to soil. In addition, this process can result in additional carbon offsets through favorable modification of soil by reducing fertilizer requirement, as well as other secondary benefits. On the other hand, biochar is typically contaminated with traces of organic (e.g., dioxins) and inorganic impurities (e.g., salts) that are detrimental to soil quality. The presence of such impurities and the capacity of the receiving soil to tolerate their presence put an upper limit on the amount of biochar that can be added without causing adverse environmental effects. Thus, scaling up biochar-based systems requires the planning of a carbon management network (CMN) consisting of biochar sources (i.e., production facilities) and biochar sinks (i.e., receiving tracts of land). In general, such CMNs need to be operated so as to maximize system-wide carbon sequestration without exceeding the tolerance limits of the biochar sinks. This paper proposes a graphical pinch analysis approach to planning such biochar-based CMNs. The applicability of the methodology is illustrated using a hypothetical case study. © 2018, Springer Nature Singapore Pte Ltd.